1994
DOI: 10.1073/pnas.91.4.1515
|View full text |Cite
|
Sign up to set email alerts
|

Design, creation, and characterization of a stable,monomeric triosephosphate isomerase.

Abstract: Protein engineering on trypanosomal triosephosphate isomerase (TIM) converted this oligomeric enzyme into a stable, monomeric protein that is enzymatically active.Wild-type TIM consists of two identical subunits that form a very tight dimer involving interactions of 32 residues of each subunit. By replacing 15 residues of the major interface loop by another 8-residue fragment, a variant was constructed that is a stable and monomeric protein with TIM activity. The length, sequence, and conformation of the desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
106
1

Year Published

1994
1994
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(113 citation statements)
references
References 24 publications
(26 reference statements)
4
106
1
Order By: Relevance
“…A stable, monomeric form of the X Cro DNA binding protein that was unable to associate into a dimer has been engineered by rather extensive rearrangement of the subunit interface to prevent productive interactions (Mossing & Sauer, 1990). A similar scheme produced an active, monomeric form of triosephosphate isomerase (Borchert et al, 1994). Surprisingly, both monomeric Cro and the isomerase had apparently higher stabilities, based on an increased T, of denaturation by 13" and 3", respectively (compared to the corresponding wild-type dimer).…”
Section: Effects Of Structural Alterations On Stabilitymentioning
confidence: 99%
“…A stable, monomeric form of the X Cro DNA binding protein that was unable to associate into a dimer has been engineered by rather extensive rearrangement of the subunit interface to prevent productive interactions (Mossing & Sauer, 1990). A similar scheme produced an active, monomeric form of triosephosphate isomerase (Borchert et al, 1994). Surprisingly, both monomeric Cro and the isomerase had apparently higher stabilities, based on an increased T, of denaturation by 13" and 3", respectively (compared to the corresponding wild-type dimer).…”
Section: Effects Of Structural Alterations On Stabilitymentioning
confidence: 99%
“…3A) as described previously for mono-TIM [8]. Since the protein concentration of the sample is approximately 1 mg/ml, the majority of the variant protein is dissociated into monomer.…”
Section: T V Borchert Et Al/febs Letters 367 (1995) 315-318mentioning
confidence: 99%
“…The Kd of the wild-type protein has been estimated to be below 10 -~1 M [8]. It has been shown that the folding pathway of the TIM-dimer can be described by a consecutive first-order folding and second-order association reaction scheme assuming inactive monomers [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations